Glial influence on the blood brain barrier. Issue 12 (7th October 2013) - Alvarez, Jorge Ivan; Katayama, Takahiro; Prat, Alexandre
<x xml:space="preserve">Abstract</x> The Blood Brain Barrier (BBB) is a specialized vascular structure tightly regulating central nervous system (CNS) homeostasis. Endothelial cells are the central component of the BBB and control of their barrier phenotype resides on astrocytes and pericytes. Interactions between these cells and the endothelium promote and maintain many of the physiological and metabolic characteristics that are unique to the BBB. In this review we describe recent findings related to the involvement of astroglial cells, including radial glial cells, in the induction of barrier properties during embryogenesis and adulthood. In addition, we describe changes that occur in astrocytes and endothelial cells during injury and inflammation with a particular emphasis on alterations of the BBB phenotype. GLIA 2013;61:1939–1958